Influência da idade na interação espermatozóide-ovo e na morfologia dos órgãos genitais em reprodutores de codornas japonesas - Carneiro, Thais Cristina (2011)
The sperm-egg interaction was investigated during their reproductive life, in laying quails mated with males of different ages (Coturnix coturnix sp.). The experimental design was completely randomized in factorial scheme 4 x 4 (age of females x age of male quail, 80,160,240 and 390 days), with 10 replicates and six birds each, in a proportion of two females for a male. The results showed that there was a quadratic effect (P <0.05) of the amount of sperm trapped in the vitelline membrane of the germinal disc, depending on the age of the females, with a reduction of this number over the age. The age of the females had no effect on egg weight, shell thickness, the percentage of shell and yolk and Haugh unit. As for the egg production there was a quadratic effect. The incubation parameters evaluated chick weight, fertility, hatchability and mortality did not differ when analyzed in relation to age of males and females, as well as egg quality and performance of the resulting progenies. The morphology of the genital organs of males and females showed no difference in the age of the birds. Males and females of laying quails maintain reproductive ability up to 56 weeks. The age of the males had no effect on the reproductive performance and the use of younger males to older females did not result in improved reproductive health.